Polygenic risk scores for the diagnosis and management of dyslipidemia. Issue 2 (15th April 2022) - Brunham, Liam R.; Trinder, Mark
Abstract : Purpose of review: To review current progress in the use of polygenic risk scores for lipid traits and their use in the diagnosis and treatment of lipid disorders. Recent findings: Inherited lipid disorders, including those causing extremes of low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, or triglycerides were initially identified as monogenic traits, in which a single rare variant with large effect size is responsible for the phenotype. More recently, a polygenic basis for many lipid traits has also been identified. Patients with polygenic dyslipidemia can be identified through the use of polygenic risk scores (PRSs), which collapse information from a handful to several million genetic variants into a single metric. Summary: PRSs for lipid traits may aid in the identification of the genetic basis for the lipid phenotype in individual patients, may provide additional information regarding the risk of cardiovascular disease, and could help in guiding therapeutic decision making.